1988
DOI: 10.1111/j.1600-0773.1988.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the in Vitro Binding of 3H‐Raclopride to Rat Striatal Dopamine‐D2 Receptors

Abstract: The influence of temperature on the in vitro binding of 3H-raclopride to rat striatal dopamine-D2 receptors was investigated. The KD-values obtained in Scatchard plots were approximately 1.6 nM at temperatures between 15 degrees and 30 degrees. At 37 degrees the KD-value was found to be 3.0 nM, indicating a lower affinity without affecting the number of the receptors (Bmax). The rate of association of 3H-raclopride to the receptors was decreased with decreasing temperatures, and at 6 degrees more than 150 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…However, previous pharmacological assays were performed almost exclusively at 41C or RT, whereas our assays were performed at 371C (to generate data that are potentially more readily related to in vivo PET data). It is not unusual or unexpected for temperature to affect the binding properties of radioligands (Hall et al, 1988(Hall et al, , 1990). Our autoradiography studies, which were performed at RT, produced K d values very similar to those reported previously (Doble et al, 1987;Miyazawa et al, 1998;Rao and Butterworth, 1997;Venneti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous pharmacological assays were performed almost exclusively at 41C or RT, whereas our assays were performed at 371C (to generate data that are potentially more readily related to in vivo PET data). It is not unusual or unexpected for temperature to affect the binding properties of radioligands (Hall et al, 1988(Hall et al, , 1990). Our autoradiography studies, which were performed at RT, produced K d values very similar to those reported previously (Doble et al, 1987;Miyazawa et al, 1998;Rao and Butterworth, 1997;Venneti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The reported in vitro value for fallypride is K D ‫ס‬ 0.03nM (t ‫ס‬ 25°C) (Mukherjee et al, 1995). For in vitro measurement of K D , substituted benzamides are known to have a large temperature dependence (Hall et al, 1988). This limits the accuracy of in vitro with in vivo K D correlations.…”
Section: In Vivo Parameters Of [F-18]fallypridementioning
confidence: 99%
“…The receptor binding studies were performed according to a previously described procedure. 27 The corpus striatum was homogenized in 50 mM Tris-HCl buffer (pH 7.7 at 25 °C) and centrifuged at 48000g for 10 min. The pellet was resuspended and centrifuged as before.…”
Section: -[3-[4-(o-butoxyphenyl)piperazin-1-yl]propyl]-13-dioxoperhyd...mentioning
confidence: 99%